If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34x + 25 = 25 + -20x Reorder the terms: 25 + 34x = 25 + -20x Add '-25' to each side of the equation. 25 + -25 + 34x = 25 + -25 + -20x Combine like terms: 25 + -25 = 0 0 + 34x = 25 + -25 + -20x 34x = 25 + -25 + -20x Combine like terms: 25 + -25 = 0 34x = 0 + -20x 34x = -20x Solving 34x = -20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20x' to each side of the equation. 34x + 20x = -20x + 20x Combine like terms: 34x + 20x = 54x 54x = -20x + 20x Combine like terms: -20x + 20x = 0 54x = 0 Divide each side by '54'. x = 0 Simplifying x = 0
| -5+w=12 | | e+18=45 | | xyz=20 | | 51=-9x-6 | | -3(n-8)=28-7n | | Y=(30-2x)(40-2x)(x) | | 4x-6x+12=20 | | 1307.2=17.2a | | 5-3x=19+4x | | 30-5v+2v=3v-12 | | 4n-12=11-4n | | 15x+8y=131 | | -131=-3-4(8-3v) | | a-20=17 | | -3m+4=-2m-5 | | 12=10y-8y | | x-7=3(x-4) | | 6-x=3(x+10) | | 10b+8b=360 | | 3075=37.5a | | 6x^2+36x+192=0 | | 5x-12=9x+5 | | 3(x+2)+1=2x-8+x+13 | | -16=2a-6a | | 637=13a | | x^2=-2+15 | | 5z=1.7+4.3 | | f(x)=6x^2+36x+192 | | x+37=129 | | 4+(m/5)=6 | | -5n-8-56m=-8 | | 4x^2+9=2x^2+3(5x+3) |